2021
DOI: 10.1155/2021/3372403
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIa Induces Autophagy and Apoptosis via PI3K/Akt/mTOR Axis in Acute Promyelocytic Leukemia NB4 Cells

Abstract: Tanshinone IIa (TanIIa), an ingredient of Radix Salviae Miltiorrhizae, has an anticancer effect on various solid tumors with high efficiency and low toxicity. Nonetheless, the underlying role of TanIIa in acute promyelocytic leukemia (APL) remains unclear. Here, we revealed that TanIIa drastically inhibited NB4 cell viability with an IC50 value of 31.25 μmol/L. Using flow cytometry apoptosis assay, we identified that TanIIa dose-dependently exacerbated NB4 cell apoptosis. Mechanistically, TanIIa upregulated ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Similarly, Ding et al (2017) found that tan IIA blocked the PI3K/Akt/mTOR pathway and lowered p-PI3K and p-Akt levels in U251 glioma cells, inducing autophagy and inhibiting cell viability. In acute promyelocytic leukemia, tan IIA blocked the PI3K/Akt/mTOR axis and promoted autophagy of NB4 cells, decreasing PI3K, Akt, and mTOR protein levels while raising p-ULK-1 and LC3B levels ( Pan et al, 2021 ). Similar to these results, tan IIA inhibited PI3K/Akt/mTOR to trigger acute myeloid leukemia U937 cell death and autophagy in vitro and in vivo ( Zhang et al, 2019c ).…”
Section: Tanshinone Induces Tumor Cell Deathmentioning
confidence: 99%
“…Similarly, Ding et al (2017) found that tan IIA blocked the PI3K/Akt/mTOR pathway and lowered p-PI3K and p-Akt levels in U251 glioma cells, inducing autophagy and inhibiting cell viability. In acute promyelocytic leukemia, tan IIA blocked the PI3K/Akt/mTOR axis and promoted autophagy of NB4 cells, decreasing PI3K, Akt, and mTOR protein levels while raising p-ULK-1 and LC3B levels ( Pan et al, 2021 ). Similar to these results, tan IIA inhibited PI3K/Akt/mTOR to trigger acute myeloid leukemia U937 cell death and autophagy in vitro and in vivo ( Zhang et al, 2019c ).…”
Section: Tanshinone Induces Tumor Cell Deathmentioning
confidence: 99%
“…Most terpenoids are isolated from medicinal plants that belong to the following plant groups: Oleaceae, Rutaceae, Labiatae, Acanthaceae, Compositae, Taxaceae, Pinaceae, Lauraceae, Araliaceae, Celastraceae, etc. Terpenoids are classified according to the number of isoprene (2-methylbuta-1, 3-diene) units into monoterpenoids (C 10 ), Menthol Peppermint oil (Mentha piperita) [17] Myrcene bay laurel oil (Laurus nobilis) and Verbena oil (Lippia citriodora) [18] Perillyl alcohol [19] Eucalyptol (1.8-cineole) Eucalyptus leaf oil (Eucalyptus globules), rosemary (Rosmarinus officinalis) [20] Sesquiterpenoids Artemisinin and its derivatives Sweet wormwood (Artemisia annua) [21] Costunolide Aucklandia lappa [22,23] Diterpenoids Acanthoic acid Acanthopanax koreanum Nakai, Croton oblongifolius Roxb [24,25] Oridonin Rabdosia rubescens [26] Tanshinone IIA Salvia miltiorrhiza Bge [27] Taxol (Paclitaxel) Taxus brevifolia [28] Triptolide Tripterygium wilfordii [29,30] Kaurenoic acid Annona senegalensis (Annonaceae) [31] Triterpenoids Celastrol Tripterygium wilfordii [29] Withaferin A Withania somnifera [32] Ursolic acid Rosmarinus officinalis (rosemary), Calluna vulgaris and Eugenia jambolana, Salvia officinalis, and Eriobotrya japonica [33] Tetraterpenoids Lycopene Tomatoes (Lycopersicon esculentum), pink guavas, apricots, water melon, and pink grapefruits [34,35] Lutein Spinach, kale, carrot, corn, and egg yolk [36,37] β-carotene Carrot [38] sesquiterpenoids (C 15 ), diterpenoids (C 20 ), triterpenoids (C 30 ), tetraterpenoids (C 40 ), and polyterpenoids (C > 40) [Table 1]. They possess vast medicinal importance that includes: antitumor, antibacterial, antimalarial, anti-inflammatory, antiviral, anticancer, immunomodulatory, anti-aging, antioxidant, anti-depressants, antifungal, and antidiabetic.…”
Section: Terpenoidsmentioning
confidence: 99%
“…It also facilitates the phagocytosis of apoptotic tumor cells through the regulation of macrophage functioning that involves tumor necrosis factor (TNF)-α and interleukin-1β. [27,59,60] It is effective against breast, colon, pancreatic, lung, gastric, prostate, and skin cancers. [61] Tanshinone IIA Its antitumor/cancer activity is attributed to its tumor growth inhibition, apoptosis induction, signaling pathway, and cell cycle regulation.…”
Section: Oridoninmentioning
confidence: 99%
“…The PI3K/Akt and MAPK/MEK/ERK1/2 signaling pathways have a positive regulatory effect on mTOR, and blocking the above pathways causes autophagy, eventually leading to tumor cell death ( Xu et al, 2020a ). It has been reported that tan I and tan IIA induce autophagy by inhibiting the PI3K/Akt/mTOR pathway, further inhibiting the proliferation of tumor cells (including ovarian cancer cells, glioma cells, acute promyelocytic leukemia NB4 cells, acute mononuclear leukemia cells, oral squamous cell carcinoma (OSCC) cells, and melanoma cells) ( Ding et al, 2017 ; Li et al, 2017 ; Qiu et al, 2018 ; Zhang et al, 2019c ; Zhou et al, 2020b ; Pan et al, 2021 ). In addition, tan IIA also drives autophagy through inhibiting the MEK/ERK/mTOR signaling pathway, thereby suppressing the proliferation of colon cancer cells ( Qian et al, 2020 ).…”
Section: Antitumor Activities Of S Miltiorrhizamentioning
confidence: 99%